Certolizumab for the treatment of psoriasis and psoriatic arthritis: a real‐world multicentre Italian study. (26th June 2020) - Dattola, A.; Balato, A.; Megna, M.; Gisondi, P.; Girolomoni, G.; De Simone, C.; Caldarola, G.; Cama, E.; Piaserico, S.; Fargnoli, M.C.; Fidanza, R.; Parodi, A.; et al.
Abstract: Background: Certolizumab, a pegylated tumour necrosis factor‐α inhibitor, reduced disease activity in randomized trials of patients with psoriasis and psoriatic arthritis. Real‐life data are missing. Objective: To confirm the effectiveness and safety of certolizumab in patients with psoriasis and psoriatic arthritis in routine clinical practice. Methods: In this retrospective study involving 11 Italian sites, patients with psoriasis and psoriatic arthritis received subcutaneous certolizumab (400 mg loading dose at 0, 2 and 4 weeks, followed by 200 mg every 2 weeks) for up to 52 weeks. Primary outcomes included mean change from baseline in Psoriasis Area and Severity Index (PASI) and modified Nail Psoriasis Severity Index (mNAPSI) scores, and the proportion of patients achieving a 75%, 90% or 100% reduction in PASI score. Other endpoints included Disease Activity Score computed on 44 joints correlated with the erythrocyte sedimentation rate during the first hour (DAS44‐ESR), Tender Joint Count (TJC), Swollen Joint Count (SJC), pain [visual analogue scale (VAS) score], inflammatory markers and quality of life (QOL). Results: In the study were enrolled 153 patients (mean age: 55 years). Certolizumab reduced the mean PASI score from baseline by 4.45, 6.30 and 7.58 at weeks 12, 24 and 52, respectively ( P < 0.001 for all). At weeks 24 and 52, 69.6% and 83.3% of patients had a PASI score ≤3. DAS44‐ESR, TJC, SJC and mNAPSI scores, and pain VAS were also all significantly improved from baseline at each time point. C‐reactive protein levels decreased during treatment, being significant at week 24. On multivariate analysis, psoriasis duration, baseline PASI, mNAPSI and pain VAS scores were found to be predictive of the improvement in PASI score at week 12. Conclusion: Certolizumab displayed also in the real‐life encouraging results in both psoriasis and psoriatic arthritis patients.